Size effect in torsional failure of normal strength and high strength concrete beams - Kumar, CH. Naga Satish; Rao, T. D. Gunneswara (Journal of Structural Engineering, 2025)
In this paper, an experimental investigation was carried out to study the size effect on the torsional failure of normal and high strength concrete beams. The main parameters in this study were size of the cross section and notch depth ratio. The current design codes IS456-2000 and ACI 318-05 formulae for the torsional failure of concrete beams exhibit no size effect, i.e. the failure of geometrically similar beams of different sizes is supposed to occur at the same stress. But from the experiments on eighteen normal strength concrete beams (NSC) and eighteen high strength concrete beams (HSC), the results confirm that there is significant size effect that is the nominal stress at failure decreases as the beam size increases. As observed in the size effect curves, the fracture behavior of HSC beams seems more brittle than that of NSC beams. The torsional strength of the HSC beams seems more size dependent than that of the NSC beams. When the specimen size increases from 75 to 300mm, the torsional strength decreases 30% only for NSC beams but 40% for the HSC beams. It was also observed that the fracture parameters i.e. fracture energy and brittleness number increasing with the increase in size of specimen and fracture energy decreases with the increasing notch depth ratios but brittleness number increases with the increasing notch depth ratio.